REPUTASI KORPORAT: UPAYA PT IMA MONTAZ SEJAHTERA (IMS) DALAM MEMELIHARA STABILITAS PERUSAHAAN - Yanuar, Deni; Saleh, Rahmat; Pratama, Dhipo (Jurnal Komunikasi Profesional, 2020)
The purpose of this research was to find out how PT. IMS Company dealt with the communication crisis and how it maintain its reputation and stability during the pre and post crisis of former employees in the company. This research used a descriptive qualitative method with a semi-structured interview in collecting the required data by interviewing 6 people consisting of 1 employee of the HRD section of PT. Ima Montaz Sejahtera and 5 people from the employees and former employees of PT. Ima Montaz Sejahtera, The theory used in this research was Situational Communication Crisis Theory (SCCT).In selecting the informants; this researched used purposive sampling method. The results showed that the company did such as socialization on the employees affected by the company. The socialization consisted of an independent business training program and severance pay. Furthermore, the company also determined to the strengthen relationship among employees by beginning to cooperate and invest on the business that have been set up by former employees. Keywords: Corporate; Reputation; Crisis.